2012
DOI: 10.1155/2012/794671
|View full text |Cite
|
Sign up to set email alerts
|

A PrioriAssessment of Algebraic Flame Surface Density Models in the Context of Large Eddy Simulation for Nonunity Lewis Number Flames in the Thin Reaction Zones Regime

Abstract: The performance of algebraic flame surface density (FSD) models has been assessed for flames with nonunity Lewis number (Le) in the thin reaction zones regime, using a direct numerical simulation (DNS) database of freely propagating turbulent premixed flames with Le ranging from 0.34 to 1.2. The focus is on algebraic FSD models based on a power-law approach, and the effects of Lewis number on the fractal dimensionDand inner cut-off scaleηihave been studied in detail. It has been found thatDis strongly affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
(108 reference statements)
4
12
0
Order By: Relevance
“…A-priori DNS analyses [6,7] suggested that η iD scales with thermal flame thickness δ th = (T ad − T 0 )/Max |∇T | L (where T is the instantaneous dimensional temperature and the subscript L refers to the unstrained premixed laminar flame condition), which is consistent with the behaviour of η i obtained previously based on experimental [31,35] and DNS [29,[32][33][34] [6,7]. The predictions of Eq.…”
Section: Mathematical Backgroundsupporting
confidence: 87%
See 4 more Smart Citations
“…A-priori DNS analyses [6,7] suggested that η iD scales with thermal flame thickness δ th = (T ad − T 0 )/Max |∇T | L (where T is the instantaneous dimensional temperature and the subscript L refers to the unstrained premixed laminar flame condition), which is consistent with the behaviour of η i obtained previously based on experimental [31,35] and DNS [29,[32][33][34] [6,7]. The predictions of Eq.…”
Section: Mathematical Backgroundsupporting
confidence: 87%
“…The DNS datasets have been explicitly filtered using the integral Q( x) = Q( x − r)G( r)d r for ranging from ≈ 0.4δ th to ≈ 2.8δ th where G( r) = (6/π 2 ) 3/2 exp(−6 r. r/ 2 ). This range of filter widths is comparable to the range of used in several previous a-priori DNS analyses [6,7,29,31,32,34,56], and span a useful range of length scales from comparable to 0.4δ th ≈ 0.71δ z (δ z = α T 0 /S L is the Zel'dovich flame thickness with α T 0 being the unburned gas thermal diffusivity) where the flame is partially resolved, up to 2.8δ th ≈ 5δ z where the flame becomes fully unresolved and is comparable to the integral length scale l.…”
Section: Numerical Implementationsupporting
confidence: 60%
See 3 more Smart Citations